Effect of thyroid dysfunction on disease activity of patients with rheumatoid arthritis - Waseem, Mir; Shah, Tabinda; Nadeem, Mir; Singh, Jaspreet; Maqbool, Saba; Dahiya, Chhaya (International Journal of Research in Medical Sciences, 2019)
Background: Rheumatoid arthritis (RA) is a chronic autoimmune systemic inflammatory multisystem disease of unknown cause that may affect many tissues and organs, but principally attacks synovial joints, primarily affecting the peripheral joints in a symmetrical pattern. The pathology of the disease process often leads to destruction of articular cartilage. It is the commonest inflammatory arthropathy worldwide with a gender predilection towards women. Prevalence of RA in the adult general population is approximately 1%. An association between RA and thyroid dysfunction with or without autoimmune origin has been reported in 6% to 34% of patients with RA. On the contrary, when presence of thyroid antibodies is considered, despite normal thyroid function, the prevalence can rise up to about 38%. These rates are significantly greater when compared with the general population. Methods: RA patients who were diagnosed according to the new 2010 EULAR/ACR criteria and thyroid function tests were done and patients with thyroid dysfunction were identified and then patients were divided into two groups based on presence of thyroid dysfunction with rheumatoid arthritis and disease activity was illustrated in both groups based on different scales. Results: In all, 250 patients 215 (86.8%) were females and 33 (13.2%) were males. ESR was elevated in 85 (34%) patients while as it was normal in 165(66%) patients. CRP was positive in 127 (52.7%) negative in 123 (47.3%) patients. Although subclinical hypothyroidism was the most frequent abnormality observed in 38.3% patients, only 30% had concomitant anti-TPO raised and 71.4% patients of overt hypothyroidism had raised anti-TPO antibody. Disease activity parameters were significantly higher in patients of RA with hypothyroidism as compared to other group. Although most of parameters of disease activity showed a higher frequency in the group having patients with thyroid disorder but the swollen joint count was comparable in both the groups and was not statistically significant. Conclusions: Presence of thyroid disorders in RA patients is suggestive of a more aggressive disease. To diagnose concurrent thyroid disorders at an earlier stage, routine measurement of serum thyroid- stimulating hormone is recommended in all RA patients at the time of diagnosis and with yearly interval thereafter.